Calcutta diary - "Mitra, Ashok" (Calcutta, 1979)
The essays in Calcutta Diary first appeared in the Economic and Political Weekly during the infamous 21-month Emergency imposed in India between June 1975 and March 1977. Interestingly, Ashok Mitra had worked with former Prime Minister Indira Gandhi who had imposed the Emergency. The essays recount aspects of a unique and particularly difficult phase in contemporary Indian history.
Keywords: Calcutta